Utilização de resíduos industriais como substratos de baixo custo para a produção de biossurfactante por Candida sphaerica - Souza Sobrinho, Humberto Bezerra de (2007)
Surfactants are amphipathic agents with application in different industries, such as the petroleum, food and pharmaceutic. Many kinds of chemical surfactants are being used nowadays, although the development of alternative products, with biodegradable nature and lower toxicity, as the so called biosurfactants, metabolites from microorganisms, is a sound strategy for the obtention of compounds with ecological acceptability and for the knowledge of specific properties and applications of these compounds. Different biosurfactants have been produced, but few are being commercialized due the production costs regarding the utilization of high cost substrates and the purification techniques. In this work, the possibility of co-utilization of two industrial residues (refinery residue and corn steep liquor) as low-cost substrates for biosurfactant production by Candida sphaerica was investigated. The yeast was cultivated in distilled water supplemented with refinery residue and cornsteep liquor in different concentrations. The results showed a reduction of the medium surface tension to 26 mN/m, with a yield of 4.0 g/L of isolated biosurfactant after 144 hours in medium containing 5.0 % refinery residue and 2.5 % cornsteep liquor. The biosurfactant was characterized as an anionic glycolipid composed of 75 % lipids and 25 % carbohydrates. The metabolic broth free of cells containing the crude biosurfactant was submitted to stability studies related to the surface tension and to the emulsification activity. The biosurfactant showed stable capacity to reduce the surface tension under extreme conditions of pH, temperature and under addition of high sodium chloride concentrations. The biopolymer can also be applied as emulsifier for specific hydrocarbons, considering the importance of the conditions of application. The biosurfactant showed a low micelar critical concentration value (0.08 %) and potential of application in soil bioremediation, which was showed throughout the motor oil removal of 65 %. Regarding the low surface tension associated to the use of industrial residues, the biosurfactant produced by Candida sphaerica shows great potential of application in industrial and environmental processes